KAJIAN PEDAGOGIK : TERHADAP DAMPAK LINGKUNGAN BELAJAR TERHADAP IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN BERFIKIR KREATIF SISWA DI SD NEGERI CIBITUNG 2 - Sukaesih; Babang Robandi; Hernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article examines how the learning environment affects the application of project-based learning models and enhances students' creative thinking abilities at SD Negeri Cibitung 2. The research seeks to determine how elements of the learning environment, including school resources, peer interactions, and educator assistance, influence the success of project-based learning approaches in improving students' creative thinking abilities. This study employs a quantitative method, gathering data through surveys and observations. The results indicate that an enabling learning environment significantly aids in the execution of project-based learning models and enhances students' creative thinking abilities.